Forum ekspertów Recent advances in anaesthesia for pulmonary endarterectomy - Webb, Stephen T.; Jenkins, David P.; Latimer, Raymond D. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a form of pulmonary hypertension (PH) that is rapidly gaining importance. The disease is associated with acute or recurrent pulmonary thromboembolism leading to chronic vascular obliteration. The result is increased pulmonary vascular resistance, the development of PH and progressive right heart failure. There have been significant advances in the diagnosis and treatment of this debilitating condition. Therapeutic options include medical therapy, lung transplantation and pulmonary endarterectomy (PEA). By the removal of obstructive material from the pulmonary arterial system, PEA improves functional status and survival for patients with CTEPH. The procedure is now considered the treatment of choice for this condition and recently there has been an expansion in the number of centres performing PEA. Success depends on a high volume of cases and a coordinated multidisciplinary team comprising physicians, radiologists, surgeons, anaesthetists and intensivists.